(untitled) - Hasik, James (New York, N.Y., 2007)
To compete for admission to a top business school in the United States, students must score in the high 600s. Conforming to the new GMAT first being administered in 2006, McGraw-Hill's GMAT is specifically written to help you achieve this crucial score or better without breaking a sweat. Filled with examples and review material geared to college-level study, this guide emphasizes the quantitative section of the exam, widely recognized as the best predictor of future performance in the business school curriculum.
Keywords: Graduate management admission test,Management,Business,Universities and colleges; Examinations, questions, etc.,Examinations, questions, etc.,Graduate work,Examinations; United States